Lifestyle for cardiovascular prevention. How relevant to the health needs of South Africa? - Opie, Lionel H. (SA Heart Journal, 2017)
The concept that the ideal lifestyle changes will improve heath and longevity may only be feasible for the fortunate few who have time, knowledge and energy to devote to this important health issue. I have called the critical five lifestyle factors the “Big Five” to help in spreading the concept.(1) Such mnemonics sound good and we all know of the health benefits but, as the saying goes, “the spirit is willing but the flesh is weak.” What is practical? How do the lifestyle Big Five fit in with the better known Risk Factor concept and the increasing number of guidelines?